Techno-economic assessment of photovoltaic-diesel generator-battery energy system for base transceiver stations loads in Nigeria. Issue 1 (1st January 2019) - Babatunde, Olubayo Moses; Denwigwe, Iheanacho Henry; Babatunde, Damilola Elizabeth; Ayeni, Augustine Omoniyi; Adedoja, Toyosi Beatrice; Adedoja, Oluwaseye Samson
Abstract: There are over 50, 000 telecommunication base transceiver stations (BTS) operating on conventional diesel generators across Nigeria, giving rise to a high operational cost and emission of Greenhouse gases which can be minimized by the adoption of greener energy generation. Presented in this study, is an analysis of the techno-economic and emission impact of a stand-alone hybrid energy system designed for base transceiver stations (BTS) in the Nigerian telecom industry. Using various performance criteria the feasibility of adopting hybrid photovoltaic-diesel generator and battery (PV/DG/Battery) system is analyzed under two different diesel pump price regimes. In all, it is observed that all BTS locations across the six geopolitical zones could adopt PV/battery/DG hybrid renewable energy system in place of the diesel generator (DG) which is, presently, the main technology being used across the BTSs. Besides its economic advantages over the diesel generator, HRES configurations also performed better with respect to diesel consumption and carbon dioxide (CO2 ) emission.